The Influence Of Tourist Facilities And Service Quality On Visitor Satisfaction At The “Dunia Fantasi (DUFAN) Taman Impian Jaya Ancol” Amusement Park - Septiana, Hana; Febriyantoro, Mohamad Trio (PT. Batari Edu Calya, 2023)
The purpose of this study was to determine and analyze the influence of tourist facilities and service quality as independent variables, while the variable visitor satisfaction is the dependent variable. The number of respondents used in this study was 112 respondents. The data used is primary data, and inanalyzing data using SPSS software. Things tested in SPSS are validity test, reliability test, classic assumption test (normality test, multicollinearity test, and heteroscedasticity test), multiple linear regression analysis, F test, and T test. The results showed that the variables of Tourism Facilities and Service Quality has a significant effect on visitor satisfaction at Dunia Fantasi, Taman Impian Jaya Ancol amusement park.